1992
DOI: 10.1111/j.1539-6924.1992.tb00703.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Neglecting Correlations When Propagating Uncertainty and Estimating the Population Distribution of Risk

Abstract: Interest in examining both the uncertainty and variability in environmental health risk assessments has led to increased use of methods for propagating uncertainty. While a variety of approaches have been described, the advent of both powerful personal computers and commercially available simulation software have led to increased use of Monte Carlo simulation. Although most analysts and regulators are encouraged by these developments, some are concerned that Monte Carlo analysis is being applied uncritically. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 17 publications
1
49
0
Order By: Relevance
“…The Supporting Information (Table S2) provides further details about the magnitude and uncertainty distributions of these parameters. We have assumed that none of the model inputs are correlated, as asserted in previous studies (14)(15)(16)(17)(18)36).…”
Section: Prior Uncertainty Distributionsmentioning
confidence: 99%
“…The Supporting Information (Table S2) provides further details about the magnitude and uncertainty distributions of these parameters. We have assumed that none of the model inputs are correlated, as asserted in previous studies (14)(15)(16)(17)(18)36).…”
Section: Prior Uncertainty Distributionsmentioning
confidence: 99%
“…Smith et al (1992) found that ignoring correlation may seriously bias the resulting risk, however, they also conclude that in some circumstances correlation can be ignored, and give a method for assessing how much effect correlation may have on results. Cicumstances in which correlations may be ignored (because they will not substantially impact results) include:…”
Section: Correlation Between Parameter Uncertainty Distributionsmentioning
confidence: 99%
“…If a dependency is neglected, the answer obtained by an analysis assuming independence will generally be wrong. Under certain conditions, the central tendency of output distributions could be approximately correct (Smith et al 1992). However, the estimated dispersion and especially the tail probabilities can be highly inaccurate (Bukowski et al 1995;Ferson and Burgman 1995;Ferson 1994).…”
Section: Unjustified Independence Assumptions Harmfulmentioning
confidence: 99%